Pengaruh Ukuran Perusahaan dan Profitabilitas terhadap Audit Report Lag di Bursa Efek Indonesia - Donianto Tandy Patiku; Eva Marin Sambo (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2015)
The phenomenon that occurs in Indonesia Stock Exchange in 2013, there were 52 listed companies were late in submitting financial statements in 2012, in 2012 recorded 54 issuers are late in submitting financial reports, in 2011 recorded 62 issuers late submit financial reports in 2010, and in 2010 recorded 68 issuers to submit financial reports late 2009. This study aims to test empirically the effect of firm size and profitability of the audit report lag in the general mining sector firm on the Indonesia Stock Exchange. Data used is secondary, the 38 firms listed on the Indonesia Stock Exchange from 2009-2012. In this study using multiple regression analysis to test the hypothesis. Simultaneously test results conclude that firm size and profitability significantly affect the audit report lag. But the partial test indicates that company size does not affect the audit report lag while profitability siginficantly negative effect on the audit report lag.